An Application of STM32F4-Embedded ANFIS-Fuzzy Controller for Tower Crane - Nguyen, Ngoc-Truong-Son; Dang, Quang-Hai; Nguyen, Dang-Khang; Lam, Duc-Quan; Nguyen, Vo-Hoai-Nam; Le, Nguyen-Phap-Tri; Tran, Nguyen-Khang; Bui, Van-The-Hieu; Nguyen, Thai-Hoa; Le, ThiHongLam (Peneliti Teknologi Teknik Indonesia, 2024)
In this paper, we examine tower crane – a MIMO under-actuated system- which is popular in both academia and industry. From a successful PID controller for this model, we design a fuzzy controller that is generated by the ANFIS toolbox from MATLAB. The proposed controller is shown to be viable based on both the simulation and experimental results obtained. In experiments, the angle of load vibrates a maximum of 10 degrees around the set angle and the settling error is a maximum of 1 degree. Also, the settling time of the trolley is a maximum of 12 sec. These results are acceptable. This control method controls positions and decreases the fluctuation of this model. In the hardware platform, STM32F4 Discovery is used as a control board, and it is well-embedded by fuzzy blocks to prove its ability in future intelligent control.